Science and Risk Communication: A Mini-Symposium Sponsored by the Roundtable on Environmental Health Sciences, Research, and Medicine - Institute of Medicine (The National Academies Press, 2001)

Basic Research Opportunities in Earth Science - National Research Council (The National Academies Press, 2001)
Basic Research Opportunities in Earth Science identifies areas of high-priority research within the purview of the Earth Science Division of the National Science Foundation, assesses cross-disciplinary connections, and discusses the linkages between basic research and societal needs. Opportunities in Earth science have been opened up by major improvements in techniques for reading the geological record of terrestrial change, capabilities for observing active processes in the present-day Earth, and computational technologies for realistic simulations of dynamic geosystems. This book examines six specific areas in which the opportunities for basic research are especially compelling, including integrative studies of the near-surface environment (the 201cCritical Zone201d); geobiology; Earth and planetary materials; investigations of the continents; studies of Earth2019s deep interior; and planetary science. It concludes with a discussion of mechanisms for exploiting these research opportunities, including EarthScope, natural laboratories, and partnerships.

Review of EarthScope Integrated Science - National Research Council
EarthScope is a major science initiative in the solid-earth sciences and has been described as \

Marijuana As Medicine?: The Science Beyond the Controversy - Institute of Medicine (The National Academies Press, 2001)
Some people suffer from chronic, debilitating disorders for which no conventional treatment brings relief. Can marijuana ease their symptoms? Would it be breaking the law to turn to marijuana as a medication? There are few sources of objective, scientifically sound advice for people in this situation. Most books about marijuana and medicine attempt to promote the views of advocates or opponents. To fill the gap between these extremes, authors Alison Mack and Janet Joy have extracted critical findings from a recent Institute of Medicine study on this important issue, interpreting them for a general audience. Marijuana As Medicine? provides patients2014as well as the people who care for them2014with a foundation for making decisions about their own health care. This empowering volume examines several key points, including: Whether marijuana can relieve a variety of symptoms, including pain, muscle spasticity, nausea, and appetite loss. The dangers of smoking marijuana, as well as the effects of its active chemical components on the immune system and on psychological health. The potential use of marijuana-based medications on symptoms of AIDS, cancer, multiple sclerosis, and several other specific disorders, in comparison with existing treatments. Marijuana As Medicine? introduces readers to the active compounds in marijuana. These include the principal ingredient in Marinol, a legal medication. The authors also discuss the prospects for developing other drugs derived from marijuana's active ingredients. In addition to providing an up-to-date review of the science behind the medical marijuana debate, Mack and Joy also answer common questions about the legal status of marijuana, explaining the conflict between state and federal law regarding its medical use. Intended primarily as an aid to patients and caregivers, this book objectively presents critical information so that it can be used to make responsible health care decisions. Marijuana As Medicine? will also be a valuable resource for policymakers, health care providers, patient counselors, medical faculty and students2014in short, anyone who wants to learn more about this important issue.

A Convergence of Science and Law: A Summary Report of the First Meeting of the Science, Technology, and Law Panel (The National Academies Press, 2001)
This report is a summary of the first meeting of the Science, Technology, and Law Panel. The Policy Division of the National Research Council established the panel to bring the science and engineering community and the legal community together on a regular basis to explore pressing issues, to improve communication, and to help resolve such issues between these communities.

Science and Technology for Environmental Cleanup at Hanford - National Research Council (The National Academies Press, 2001)
The Hanford Site was established by the federal government in 1943 as part of the secret wartime effort to produce plutonium for nuclear weapons. The site operated for about four decades and produced roughly two thirds of the 100 metric tons of plutonium in the U.S. inventory. Millions of cubic meters of radioactive and chemically hazardous wastes, the by-product of plutonium production, were stored in tanks and ancillary facilities at the site or disposed or discharged to the subsurface, the atmosphere, or the Columbia River. In the late 1980s, the primary mission of the Hanford Site changed from plutonium production to environmental restoration. The federal government, through the U.S. Department of Energy (DOE), began to invest human and financial resources to stabilize and, where possible, remediate the legacy of environmental contamination created by the defense mission. During the past few years, this financial investment has exceeded 1 billion annually. DOE, which is responsible for cleanup of the entire weapons complex, estimates that the cleanup program at Hanford will last until at least 2046 and will cost U.S. taxpayers on the order of 85 billion. Science and Technology for Environmental Cleanup at Hanford provides background information on the Hanford Site and its Integration Project,discusses the System Assessment Capability, an Integration Project-developed risk assessment tool to estimate quantitative effects of contaminant releases, and reviews the technical elements of the scierovides programmatic-level recommendations.

Classroom Assessment and the National Science Education Standards - National Research Council (The National Academies Press, 2001)
The National Science Education Standards address not only what students should learn about science but also how their learning should be assessed. How do we know what they know? This accompanying volume to the Standards focuses on a key kind of assessment: the evaluation that occurs regularly in the classroom, by the teacher and his or her students as interacting participants. As students conduct experiments, for example, the teacher circulates around the room and asks individuals about their findings, using the feedback to adjust lessons plans and take other actions to boost learning. Focusing on the teacher as the primary player in assessment, the book offers assessment guidelines and explores how they can be adapted to the individual classroom. It features examples, definitions, illustrative vignettes, and practical suggestions to help teachers obtain the greatest benefit from this daily evaluation and tailoring process. The volume discusses how classroom assessment differs from conventional testing and grading-and how it fits into the larger, comprehensive assessment system.

Educating Teachers of Science, Mathematics, and Technology: New Practices for the New Millennium - National Research Council (The National Academies Press, 2001)
Each new headline about American students' poor performance in math and science leads to new calls for reform in teaching. Education Teachers of Science, Mathematics, and Technology puts the whole picture together by synthesizing what we know about the quality of math and science teaching, drawing conclusions about why teacher preparation needs reform, and then outlining recommendations for accomplishing the most important goals before us. As a framework for addressing the task, the book advocates partnerships among school districts, colleges, and universities, with contributions from scientists, mathematicians, teacher educators, and teachers. It then looks carefully at the status of the education reform movement and explores the motives for raising the bar for how well teachers teach and how well students learn. Also examined are important issues in teacher professionalism: what teachers should be taught about their subjects, the utility of in-service education, the challenge of program funding, and the merits of credentialing. Professional Development Schools are reviewed and vignettes presented that describe exemplary teacher development practices.

Issues for Science and Engineering Researchers in the Digital Age - National Research Council (The National Academies Press, 2001)

Science, Evidence, and Inference in Education: Report of a Workshop - National Research Council (The National Academies Press, 2001)
Research on education has come into the political spotlight as the demand grows for reliable and credible information for the guidance of policy and practice in the education reform environment. Many debates among the education research community feature questions concerning the nature of evidence and these questions have also appeared in broader policy and practice arenas. Inquiry has generally, over the past years, created bodies of scientific knowledge that have profound implications for education. Dramatic advances in understanding how people learn, how young children acquire early reading skills, and how to design and evaluate educational and psychological measurements is a good example of this. However, the highly contextualized nature of education and the wide range of disciplinary perspectives that rely on it have made the identification of reducible, generalizable principles difficult and slow to achieve. Due to this, the U.S. Department of Education's National Educational Research Policy and Priorities Board (NERPPB) has asked the NRC to establish a study committee to consider the scientific underpinnings of research in education. The committee consists of members with expertise in statistics, psychology, sociology, anthropology, philosophy of science, history of education, economics, chemistry, biology, and education practice. The committee worked with the three questions in mind: What are the principles of scientific quality in education research?, How can research-based knowledge in education cumulate?, and How can a federal research agency promote and protect scientific quality in the education research it supports?. A workshop was held on March 7-8, 2001 that was organized into three main sessions: Supporting Scientific Quality at the Federal level, The Interface of Research and Practice in Education, and Evidence and Inference. Science, Evidence, and Inference in Education: Report of a Workshop summarizes this workshop through these three ideas. The report also includes what the committee plans to do next, the workshop agenda, and information on the workshop's participants and speakers.

Climate Change Science: An Analysis of Some Key Questions - National Research Council (The National Academies Press, 2001)
The warming of the Earth has been the subject of intense debate and concern for many scientists, policy-makers, and citizens for at least the past decade. Climate Change Science: An Analysis of Some Key Questions, a new report by a committee of the National Research Council, characterizes the global warming trend over the last 100 years, and examines what may be in store for the 21st century and the extent to which warming may be attributable to human activity.

The Science of Regional and Global Change: Putting Knowledge to Work - National Research Council (The National Academies Press, 2001)
This report is intended to promote a dialogue between the scientific community and the government officials who will lead our nation in the coming years on global change research. The first section of the report is a brief description of the challenges and proposed responses needed from the highest levels of the government and the second provides more detailed discussion and is directed to agency-level issues and responses. The last section is a detailed bibliography that lists many of the specific reports on which the views outlined here are ultimately based.

Knowing What Students Know: The Science and Design of Educational Assessment - National Research Council (The National Academies Press, 2001)
Education is a hot topic. From the stage of presidential debates to tonight's dinner table, it is an issue that most Americans are deeply concerned about. While there are many strategies for improving the educational process, we need a way to find out what works and what doesn't work as well. Educational assessment seeks to determine just how well students are learning and is an integral part of our quest for improved education. The nation is pinning greater expectations on educational assessment than ever before. We look to these assessment tools when documenting whether students and institutions are truly meeting education goals. But we must stop and ask a crucial question: What kind of assessment is most effective? At a time when traditional testing is subject to increasing criticism, research suggests that new, exciting approaches to assessment may be on the horizon. Advances in the sciences of how people learn and how to measure such learning offer the hope of developing new kinds of assessments-assessments that help students succeed in school by making as clear as possible the nature of their accomplishments and the progress of their learning. Knowing What Students Know essentially explains how expanding knowledge in the scientific fields of human learning and educational measurement can form the foundations of an improved approach to assessment. These advances suggest ways that the targets of assessment-what students know and how well they know it-as well as the methods used to make inferences about student learning can be made more valid and instructionally useful. Principles for designing and using these new kinds of assessments are presented, and examples are used to illustrate the principles. Implications for policy, practice, and research are also explored. With the promise of a productive research-based approach to assessment of student learning, Knowing What Students Know will be important to education administrators, assessment designers, teachers and teacher educators, and education advocates.

Cells and Surveys: Should Biological Measures Be Included in Social Science Research? - National Research Council (The National Academies Press, 2001)
What can social science, and demography in particular, reasonably expect to learn from biological information? There is increasing pressure for multipurpose household surveys to collect biological data along with the more familiar interviewer-respondent information. Given that recent technical developments have made it more feasible to collect biological information in non-clinical settings, those who fund, design, and analyze survey data need to think through the rationale and potential consequences. This is a concern that transcends national boundaries. Cells and Surveys addresses issues such as which biologic\/genetic data should be collected in order to be most useful to a range of social scientists and whether amassing biological data has unintended side effects. The book also takes a look at the various ethical and legal concerns that such data collection entails.

Good Seeing: A Century of Science at the Carnegie Institution of Washington, 1902-2002 - James Trefil; Margaret Hindle Hazen; Timothy Ferris
Good Seeing presents a readable, inspiring history of the Carnegie Institution of Washington, from its founding in 1902, through the emergence of \

Observations on the President's Fiscal Year 2002 Federal Science and Technology Budget - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2001)
Fourth in a series of annual reports, this study provides observations on the Administration's FY 2002 budget proposal for federal science and technology (FS&T) programs. The report comments first on approaches to tabulating federal spending on FS&T and endorses the Administration's method for developing an FS&T budget cross-tabulation for inclusion in its budget proposal. The report then provides observations on the FY 2002 FS&T budget proposal, identifying changes in FS&T investments by federal agencies from the prior year; and assessing the longer-term impacts of these FS&T proposals in various fields.

Data for Science and Society: Proceedings of the Second National Conference on Scientific and Technical Data (The National Academies Press, 2001)
In conjunction with several federal science agencies, the U.S. National Committee for CODATA organized the Second National Conference on Scientific and Technical Data: Data for Science and Society to address important multidisciplinary issues in managing and using scientific and technical (S&T) data and to improve the visibility of these issues nationally. The main focus was on promoting the availability and usefulness of S&T data to all users, both in research and in the broader society, using examples of ground-breaking and innovative applications and highly creative partnerships. The conference was held on March 13-14, 2000, at the National Academy of Sciences in Washington, D.C., and included a set of plenary presentations by invited speakers, as well as contributed poster presentations and technical demonstrations. These proceedings from the conference include only the invited plenary presentations. These presentations have been edited and reviewed according to standard National Research Council procedures, although they are included in this volume as the contributions of each individual speaker.

Food Safety Policy, Science, and Risk Assessment: Strengthening the Connection: Workshop Proceedings - Institute of Medicine
The Institute of Medicine's (IOM's) Food Forum was established in 1993 to allow science and technology leaders in the food industry, top administrators in several federal government agencies from the United States and Canada, representatives from consumer interest groups, and academicians to openly communicate in a neutral setting. The Food Forum provides a mechanism for these diverse groups to discuss food, food safety, and food technology issues and to identify possible approaches for addressing these issues by taking into consideration the often complex interactions among industry, regulatory agencies, consumers, and academia. The objective, however, is to illuminate issues, not to resolve them. Unlike study committees of the IOM, forums cannot provide advice or recommendations to any government agency or other organization. Similarly, workshop summaries or other products resulting from forum activities are precluded from reaching conclusions or recommendations but, instead, are intended to reflect the variety of opinions expressed by the participants. On July 13-14, 1999, the forum convened a workshop on Food Safety Policy, Science, and Risk Assessment: Strengthening the Connection. The purpose of the workshop was to address many of the issues that complicate the development of microbiological food safety policy, focusing on the use of science and risk assessment in establishing policy and in determining the utilization of food safety resources. The purpose was not to find fault with past food safety regulatory activities or food safety policy decisions. Rather, the goal was to determine what actions have been taken in the past to address food safety issues, to consider what influences led to the policies that were put in place, and to explore how improvements can be made in the future. This report is a summary of the workshop presentations. It is limited to the views and opinions of those invited to present at the workshop and reflects their concerns and areas of expertise. As such, the report does not provide a comprehensive review of the research and current status of food safety policy, science, and risk assessment. The organization of the report approximates the order of the presentations at the workshop. The identification of a speaker as an \

Enhancing NASA's Contributions to Polar Science: A Review of Polar Geophysical Data Sets - National Research Council
The high latitudes of the Arctic and Antarctic, together with some mountainous areas with glaciers and long-lasting snow, are sometimes called the cryosphere-defined as that portion of the planet where water is perennially or seasonally frozen as sea ice, snow cover, permafrost, ice sheets, and glaciers. Variations in the extent and characteristics of surface ice and snow in the high latitudes are of fundamental importance to global climate because of the amount of the sun's radiation that is reflected from these often white surfaces. Thus, the cryosphere is an important frontier for scientists seeking to understand past climate events, current weather, and climate variability. Obtaining the data necessary for such research requires the capability to observe and measure a variety of characteristics and processes exhibited by major ice sheets and large-scale patterns of snow and sea ice extent, and much of these data are gathered using satellites.As part of its efforts to better support the researchers studying the cryosphere and climate, the National Aeronautics and Space Administration (NASA)-using sophisticated satellite technology-measures a range of variables from atmospheric temperature, cloud properties, and aerosol concentration to ice sheet elevation, snow cover on land, and ocean salinity. These raw data are compiled and processed into products, or data sets, useful to scientists. These so-called \

Clearing the Smoke: Assessing the Science Base for Tobacco Harm Reduction - Institute of Medicine
Despite overwhelming evidence of tobacco's harmful effects and pressure from anti-smoking advocates, current surveys show that about one-quarter of all adults in the United States are smokers. This audience is the target for a wave of tobacco products and pharmaceuticals that claim to preserve tobacco pleasure while reducing its toxic effects. Clearing the Smoke addresses the problems in evaluating whether such products actually do reduce the health risks of tobacco use. Within the context of regulating such products, the committee explores key questions: Does the use of such products decrease exposure to harmful substances in tobacco? Is decreased exposure associated with decreased harm to health? Are there surrogate indicators of harm that could be measured quickly enough for regulation of these products? What are the public health implications? This book looks at the types of products that could reduce harm and reviews the available evidence for their impact on various forms of cancer and other major ailments. It also recommends approaches to governing these products and tracking their public health effects. With an attitude of healthy skepticism, Clearing the Smoke will be important to health policy makers, public health officials, medical practitioners, manufacturers and marketers of \